Integrated Computational Life Cycle Engineering for Traction Batteries - Cerdas, Felipe; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The environmental burden caused by private transportation represents a significant challenge towards sustainability. Electric vehicles are considered a key technology to reduce the environmental impact caused by the mobility sector. However, the global adoption of electromobility implies shift and diversification of the environmental impacts caused by the transportation sector mainly driven by the production of the battery system. Modeling the life cycle environmental impacts of traction batteries is a time demanding and interdisciplinary task as it involves a high variability and requires an in-depth knowledge of the product system under analysis. To face these challenges, an Integrated Computational Life Cycle Engineering ICLCE framework for EVs has been developed. The ICLCE framework described aims at supporting fast and comprehensive modelling of complex foreground systems in the electromobility field and their interaction with diverse backgrounds and partial contexts.
Background and context -- LCE and electromobility -- State of Research -- Concept Development -- Exemplary application -- Summary, critical review and outlook. .
Keywords: Industrial engineering; Production engineering; Earth sciences; Geography; Computer-aided engineering; Industrial and Production Engineering; Earth and Environmental Sciences; Computer-Aided Engineering (CAD, CAE) and Design; Electric vehicles -- Batteries -- Environmental aspects; Electric vehicles -- Batteries